Coevolution of SOEs and the Chinese economy: The roles of SOE heterogeneity from the institutional, strategic, and organizational perspectives - HUANG, Kenneth G. (Institutional Knowledge at Singapore Management University, 2025)
State-owned enterprises (SOEs) in China play a critical role in national economic development and the country's positioning on the global stage. Chinese SOEs have undergone substantial transformations from traditional government-run entities to a variety of corporate forms exhibiting different levels of state involvement. Despite their substantial influence, the internal diversity of SOEs – from wholly state-owned to mixed-ownership – has not been thoroughly examined. This paper provides an overview of SOEs' critical roles in the Chinese economy, the relationship between SOEs and privately owned enterprises (POEs), and the challenges of SOEs in different stages of Chinese economic development. It then introduces five research papers that explore the institutional, strategic, and organizational perspectives on how SOEs manage the dual pressures of state and market logic, respond to policy adjustments, tackle leadership challenges, and navigate current global trends such as digital transformation, technological innovation, and environmental sustainability. In this paper, we provide important implications for policy and managerial practices and highlight a future research agenda for the heterogeneity of Chinese SOEs, and how SOEs respond to these challenges in the evolving geopolitical landscape, adapt their strategies, and manage relationships with foreign governments and enterprises under such conditions.